1974
DOI: 10.1901/jaba.1974.7-299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cueing on Self‐control of Classroom Behavior

Abstract: AUCKLAND PSYCHOLOGICAL SERVICEBehavioral self-control procedures, composed of self-assessment, self-recording, selfdetermination and administration of reinforcement, were introduced into a regular third-grade classroom immediately after a baseline period. The procedures produced a small and unstable increase in the level of on-task behavior in eight of the nine subjects. After a second baseline period, a cueing procedure was introduced, using a chart specifying on-task behavior. This enabled within-lesson chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
32
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…However, studies using self-management or self-control procedures with other populations have identified and found effective several behavioral components including selfassessment and self-recording (Bandura and Perloff, 1967;Glynn, Thomas, and Shee, 1973). Glynn and Thomas (1974) used a chart representing on-task behavior as a cueing procedure. The chart combined with a self-control procedure produced an increase in on-task behavior in 355 1979, 125 355-361 NUMBER 3 (FALL 1979) students in a third-grade classroom.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies using self-management or self-control procedures with other populations have identified and found effective several behavioral components including selfassessment and self-recording (Bandura and Perloff, 1967;Glynn, Thomas, and Shee, 1973). Glynn and Thomas (1974) used a chart representing on-task behavior as a cueing procedure. The chart combined with a self-control procedure produced an increase in on-task behavior in 355 1979, 125 355-361 NUMBER 3 (FALL 1979) students in a third-grade classroom.…”
mentioning
confidence: 99%
“…The Glynn and Thomas (1974) washed pots and pans, and Chuck worked in a separate dishroom. All subjects had been assigned to their current jobs for more than 2 mo.…”
mentioning
confidence: 99%
“…Self-assessment has been characterized as one component of self-management in which students evaluate their own ongoing performance and furnish a form of self-feedback in accordance with the standards set forth by some external mechanism or socializing agent (Glynn & Thomas, 1974). For at least the last 25 years, self-assessment has been a popular intervention strategy and a source of highly diversified applied research in school settings (Ninness & Glenn, 1988).…”
mentioning
confidence: 99%
“…On-task behaviors increased dramatically, and independent observers indicated that 76% of the students' self-assessed on-task recordings agreed with those of trained observers. Glynn and Thomas (1974) replicated this strategy using an intermittent audio signal to cue selfassessment intervals. Likewise, Maag et al (1993) found that improved academic accuracy or academic productivity was associated with selfmonitoring even when no feedback for correct self-recordings was provided.…”
mentioning
confidence: 99%
“…Glynn and Thomas (1974), in attempting to modify on-task behavior in a classroom, found that a self-evaluation procedure not preceded by a teacher-evaluation condition was effective. However, Santogrossi et al (1973) and Turkewitz, O'Leary, and Ironsmith (1975) did not achieve a successful child-evaluation treatment for disruptive behavior until after a period of intermittent teacher checks on child evaluations.…”
mentioning
confidence: 99%